Лесная красавица: [новогодние сказки] / Т. Комзалова ; [худ. С. Самсоненко] - Комзалова Т. А. (Читаем сами, 2015)
Экземпляры: ДО (20161018) / Инвентарный номер: 52570 / Цена: 65.00 / Авт.знак: К63 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6